2022
DOI: 10.3390/children9101540
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-Associated Pneumonia Prevention in Pediatric Patients: Narrative Review

Abstract: Ventilator-associated pneumonia (VAP), one of the most common healthcare-associated infections in intensive care settings, is associated with significant morbidity and mortality. VAP is diagnosed in >10% of patients on mechanical ventilation, incidence rising with number of ventilator days. In recent decades, the pathophysiology of VAP, VAP risk factors and treatment have been extensively studied. In critically ill pediatric patients, mechanical issues such as insufficient tightness of the ventilator circui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
(118 reference statements)
0
4
0
Order By: Relevance
“…Most of the studies included patients with VAP only. Moreover, the nutritional status, diagnostic criteria and resource availability can be the source of differences in the prevalence of VAP [58]. One study conducted in a tertiary care hospital in Riyadh reported a VAP incidence rate of 15.4%, which is higher than the global average of 7-8% [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies included patients with VAP only. Moreover, the nutritional status, diagnostic criteria and resource availability can be the source of differences in the prevalence of VAP [58]. One study conducted in a tertiary care hospital in Riyadh reported a VAP incidence rate of 15.4%, which is higher than the global average of 7-8% [39].…”
Section: Discussionmentioning
confidence: 99%
“…Another study in a pediatric intensive care unit in Jeddah reported a VAP rate of 10.2% [33]. However, the pediatric studies all around the world reported the VAP prevalence of 2-35% [58][59][60][61]. The most common pathogens responsible for VAP include gram-negative bacteria such as Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumoniae, as well as gram-positive bacteria such as Staphylococcus aureus and Streptococcus pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…3 This type of support is essential for patients with altered respiratory function, which impairs gas exchange, oxygen supply for tissue perfusion, and cellular reactions. 4 Pneumonia arises in response to the invasion of microorganisms into the lower respiratory system and lung parenchyma. Intubation compromises the integrity of the oropharynx and trachea, potentially enabling gastric and oral secretions to enter the lower airways.…”
Section: Introductionmentioning
confidence: 99%
“…Several pediatric studies report that the frequency of VAP in the Pediatric Intensive Care Units (PICUs) worldwide is in the range of 2 to 35%. Such significant variation is attributed to, among other things, differences in case definition, sampling procedure and diagnostic method [5,6]. The most recent National Health Safety Network (NHSN) module published by the Centers for Disease Control and Prevention on definitions specific to VAP underlines that early-onset VAP is suspected when microorganism invasion of the lower respiratory tract occurs on more than two consecutive calendar days from the date of event in patients on mechanical ventilator support [7].…”
Section: Introductionmentioning
confidence: 99%